Prevalence of Non-alcoholic Fatty Liver Disease - A Population Based Study (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Non alcoholic fatty liver disease (NAFLD) is defined as the accumulation of excess fat in the liver in the absence of significant alcohol consumption. NAFLD is a common cause of chronic liver disease. The overall prevalence of NAFLD in western countries varies from 15-40% and in Asian 9-40%. Its prevalence has not been determined in population based study in Bangladesh.The objective of the study was to determine the prevalence and risk factors of NAFLD in adult rural population.Methods: This cross-sectional study was performed among adult population of two villages of Comilla district, Bangladesh from January to December 2015. Persons with alcohol consumption and other liver diseases were excluded. Individuals were undergone anthropometric, blood pressure measurements, thorough medical history and physical examinations. Laboratory measurements included were fasting blood sugar (FBS), fasting lipid profile, and liver function tests. NAFLD was diagnosed by transabdominal ultrasonography. Statistical analyses were performed using the SPSS software, version16.0.Results: Among 665 subjects, 213 were males (32%) and 452 were females (68%) with the mean age of 42.2 ± 15.04 years. NAFLD was diagnosed in 33% subjects. NAFLD were high in 41-60 age group (48.7%) and in female gender (P=